MicroRNAs in Plant Development and Stress Responses - Sunkar, Ramanjulu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Precise regulation of gene expression in both time and space is vital to plant growth, development and adaptation to biotic and abiotic stress conditions. This is achieved by multiple mechanisms, with perhaps the most important control being exerted at the level of transcription. However, with the recent discovery of microRNAs another ubiquitous mode of gene regulation that occurs at the post-transcriptional level has been identified. MicroRNAs can silence gene expression by targeting complementary or partially complementary mRNAs for degradation or translational inhibition. Recent studies have revealed that microRNAs play fundamental roles in plant growth and development, as well as in adaptation to biotic and abiotic stresses. This book highlights the roles of individual miRNAs that control and regulate diverse aspects of plant processes.
Small RNAs in Plants -- Role of microRNA miR319 in Plant Development -- The Roles of miR156 and miR172 in Phase Change Regulation -- Roles of miR156 and miR172 in Reproductive Development -- Trans-acting Small Interfering RNAs: Biogenesis, Mode of Action and Role in Plant Development -- Role of miRNAs in Seed Development -- Genetic and Molecular Approaches to Assess microRNA Function -- Functions of miRNAs in Rice -- microRNA Regulation of Symbiotic Nodule Development in Legumes -- Roles of miRNAs in Nutrient Signaling and Homeostasis -- Role of microRNAs in Plant Adaptation to Environmental Stresses -- Endogenous Small RNAs and Antibacterial Resistance in Plants -- Role of Virus-derived Small RNAs in Plant Antiviral Defense: Insights from DNA Viruses.
Keywords: Life sciences; Biochemistry; Plant anatomy; Plant breeding; Plant diseases; Plant physiology; Life Sciences; Plant Physiology; Plant Anatomy/Development.; Plant Biochemistry; Plant Genetics & Genomics; Plant Pathology